2014
DOI: 10.1371/journal.pone.0086950
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-Associated Bacterial Microbiome of the Gastrointestinal Tract of Weaned Pigs and Dynamics Linked to Dietary Calcium-Phosphorus

Abstract: Dietary composition largely influences pig’s gastrointestinal microbiota and represents a useful prophylactic tool against enteric disturbances in young pigs. Despite the importance for host-microbe interactions and bacterial colonization, dietary responses of the mucosa-associated bacterial communities are less well investigated. In the present study, we characterized the mucosa-associated bacterial communities at the Pars non-glandularis of the stomach, ileum and colon, and identified shifts in these communi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(116 citation statements)
references
References 53 publications
6
107
0
3
Order By: Relevance
“…Epithelium attached microbial communities have biological roles that should be characterized. A high bacterial diversity was observed in the Pars non glandularis of the pig stomach (Mann et al, 2014) and previous reports in rats and humans have found differences between the microbial counts in the colonic mucosa and feces (Zoetendal et al, 2002; Haange et al, 2012). …”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Epithelium attached microbial communities have biological roles that should be characterized. A high bacterial diversity was observed in the Pars non glandularis of the pig stomach (Mann et al, 2014) and previous reports in rats and humans have found differences between the microbial counts in the colonic mucosa and feces (Zoetendal et al, 2002; Haange et al, 2012). …”
Section: Introductionmentioning
confidence: 75%
“…The crop is dominated by Lactobacillus (Hagen et al, 2005; Stanley et al, 2014; Witzig et al, 2015), explaining the higher values of similarity and its simple structured microbiota when compared to other sections of the GIT. In ileum and caeca sections, the more diverse microbial communities are responsible for phytate degrading activities (Palacios et al, 2008), degrading complex organic substrates, and to the production of short chain fatty acids (SCFA; Stanley et al, 2013b; Mann et al, 2014; Choi et al, 2015). The average similarity decreased in these sections, perhaps related to the presence of a higher number of OTUs.…”
Section: Resultsmentioning
confidence: 99%
“…Our data indicate that the increase in numbers of GCs may constitute part of an innate defense mechanism in response to the exogenous addition of bacteria and that the gut microbiota may be a determinant for modifying the GCs. However, the primary results of this study require further confirmation with analysis of goblet cell function and bacterial diversity in the same intestine sites, considering that locationspecific microbial communities vary along the intestinal tract of pigs (17).…”
Section: Discussionmentioning
confidence: 92%
“…In the intestine, the transcriptional activation of the atonal homolog 1 gene (Atoh1) promotes the secretory GC lineage (16). There is a very high diversity of mucosa-associated microbiota in weaned pigs, and pyrosequencing analysis of the 16S rRNA gene amplicon revealed that 132 and 198 operational taxonomic units (OTUs) were assigned in the mucosa of the ileum and the colon, respectively (17).…”
mentioning
confidence: 99%
“…DNA from luminal content and gut mucosa samples was extracted using the PowerSoil® DNA Isolation Kit (MoBio Laboratories, Carlsbad, CA, USA) as described previously (Mann et al, 2014; Yasuda et al, 2015). The same protocol of DNA extraction was applied to luminal content and gut mucosa.…”
Section: Methodsmentioning
confidence: 99%